2012
DOI: 10.1021/bi301103j
|View full text |Cite
|
Sign up to set email alerts
|

Denaturation of RNA Secondary and Tertiary Structure by Urea: Simple Unfolded State Models and Free Energy Parameters Account for Measured m-Values

Abstract: To investigate the mechanism by which urea destabilizes RNA structure, urea-induced unfolding of four different RNA secondary and tertiary structures was quantified in terms of an m-value, the rate at which the free energy of unfolding changes with urea molality. From literature data and our osmometric study of a backbone analog, we derived average interaction potentials (per Å2 of solvent accessible surface) between urea and three kinds of RNA surfaces: phosphate, ribose, and base. Estimates of the increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 66 publications
12
97
1
Order By: Relevance
“…An example is the mechanism of open complex formation and stabilization in transcription initiation by Escherichia coli RNA polymerase (RNAP) at a DNA promoter (47). Here, information about interactions of solutes and noncoulombic (Hofmeister) interactions of salt ions with nucleic acid functional groups is also needed; this has been obtained for urea (11,12), and research with other solutes and salts is in progress. The small effects of urea and Hofmeister salts on the rate and equilibrium constants for the step involving opening of 13 bp of duplex promoter DNA provide evidence that RNAP opens this region in the active site cleft (14,48,49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An example is the mechanism of open complex formation and stabilization in transcription initiation by Escherichia coli RNA polymerase (RNAP) at a DNA promoter (47). Here, information about interactions of solutes and noncoulombic (Hofmeister) interactions of salt ions with nucleic acid functional groups is also needed; this has been obtained for urea (11,12), and research with other solutes and salts is in progress. The small effects of urea and Hofmeister salts on the rate and equilibrium constants for the step involving opening of 13 bp of duplex promoter DNA provide evidence that RNAP opens this region in the active site cleft (14,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…The large effects of urea, glycine betaine, and different Hofmeister salts on the subsequent step(s) that stabilize the initial open complex provide evidence for large-scale coupled folding and assembly of mobile elements of RNAP to form a clamp on the downstream duplex DNA (14,(48)(49)(50). Solutes are also excellent probes of intermediates and TS for RNA folding, because burial of base ASA is disfavored by all solutes whereas burial of backbone ASA is favored by some solutes (12,13 (Table S5). Free energies are arbitrarily chosen; only the ASA scale is quantitative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of cosolutes on RNA folding were not significantly investigated until the last decade. Studies on RNAs with either secondary and/or tertiary structures report that cosolutes such as betaine, proline, and methanol, almost always destabilize secondary structures, while having mixed effects on tertiary structure (Lambert & Draper, 2007; Lambert & Draper, 2012; Lambert et al, 2010; Soto et al, 2007). Several osmolytes have been shown to interact with the nucleobase, sugar, and phosphate of RNAs, with examples of both favorable and unfavorable interactions (Lambert & Draper, 2007).…”
Section: Bridging the Gap Between In Vitro And In Vivo Rna Foldingmentioning
confidence: 99%
“…Experimental studies have shown that RNA undergoes denaturation in the presence of urea, and such studies are useful in monitoring the unfolding pathways and the associated thermodynamic changes. 37 Chemical denaturants such as urea, guanidinium chloride, and alcohols have been commonly used to elucidate protein folding pathways and also to probe the intramolecular interactions that stabilize the native state of proteins. 817 While the molecular mechanism by which urea destabilizes proteins has been a subject of several investigations, how urea facilitates RNA unfolding is not well understood.…”
Section: Introductionmentioning
confidence: 99%